ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT ANEKA GAS INDUSTRI Tbk. - Aisyah Fitri Pasaribu; Raihan Saputra; Budi Dharma (Gapenas Publisher, 2023)
Financial statements are one of the most important things for every company, used to evaluate company performance and used to compare the company's current state with previous years. By utilizing the balance sheet and income statement as financial statements, this study seeks to evaluate the financial performance of PT Aneka Gas Tbk. This study uses a quantitative method with a comparative method, namely to compare (comparison) the performance of the company PT. Aneka Gas Tbk from 2020-2021 using financial ratio analysis including profitability, liquidity and solvency ratios. The results of the analysis show that the capability of PT Aneka Gas Tbk. in the 2018-2021 period there was a decline that occurred due to the covid 19 pandemic which caused demand for gas in the market to decrease and resulted in a decrease in gas factory production